A glycol nanomedicine via a metal-coordination supramolecular self-assembly strategy for drug release monitoring and chemo-chemodynamic therapy. Issue 20 (21st February 2022) - Li, Jiahui; Wang, Yi; Pei, Zhichao; Pei, Yuxin
Abstract : We report a glycol nanomedicine based on a metal-coordination supramolecular self-assembly strategy for targeting drug delivery and release monitoring, as well as synergistic chemo-chemodynamic therapy. Abstract : A glycol nanomedicine based on a metal-coordination supramolecular self-assembly strategy of GluCC (a copper complex of glucose modified coumarin derivative) and a chemotherapeutic agent of doxorubicin (DOX) was successfully developed. In vitro studies revealed that the nanomedicine achieved drug target delivery and release monitoring. The anti-cancer efficiency could be enhanced through synergistic therapy of chemotherapy (CT) and chemodynamic therapy (CDT). It may gain important applications in drug tracking and CDT-combined cancer therapy.